Pengaruh modal kerja terhadap profitabilitas pada perusahaan food and beverages di Bursa Efek Indonesia - Arinda Putri Nawalani; Wiwik Lestari (Journal of Business & Banking, 2015)
Working capital is defined as capital used by companies to finance daily operations. Working capital can also be interpreted as the whole current assets owned by a company. Working capital is expressed as current assets or short-term assets, such as; cash, mar-ketable securities, accounts receivable, inventory, and other current assets. The purpose of this study is to test the effect of working capital turnover, cash turnover, receivables turnover, and inventory turnover on the profitability of Food and Beverages companies listed in Indonesia Stock Exchange during 2007-2012. There are 15 companies used as the sample. They were analyzed using Eviews program and the results showed that working capital turnover has partially significant positive effect on profitability. Fur-thermore cash flows, receivables turnover, and inventory partially have significant but negative effect on profitability. These findings mean that the higher working capital turnover is the higher profitability. Therefore, the companies should also maintain the low level of working capital in order to optimizing profit.